CRIMINAL LAW OFFENSE OF OMISSION - Jonathan Christian; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
Study This study accountability criminal for someone who knows existence agreement wicked For do dangerous crimes​ security general However No report it to party authorized . Research This use method juridical normative with statute approach and conceptual approach, as well as referring to the Criminal Code and literature law related . The object of the research is the case of YD who heard plan burning House service Head of Prison However No report until the event occurred . The results of the research show that YD fulfills elements of Article 164 of the Criminal Code, namely know existence agreement evil , have time For prevent , but intentionally not​ to inform to police or victim. YD is also considered capable responsible answer in a way law Because No proven own disturbance psychological . Research conclusions This confirm that YD's actions fulfill element accountability criminal in form intention ( dolus eventualis ). Findings This expected can increase awareness public will obligation report agreement evil and become references for prosecutor in formulate charges in the case similar .